Fangchinoline Inhibits Human Esophageal Cancer by Transactivating ATF4 to Trigger Both Noxa-Dependent Intrinsic and DR5-Dependent Extrinsic Apoptosis - Zhang, Yunjing; Wang, Shiwen; Chen, Yukun; Zhang, Junqian; Yang, Jing; Xian, Jingrong; Li, Lihui; Zhao, Hu; Hoffman, Robert M.; Zhang, Yanmei; Jia, Lijun (Frontiers in Oncology, 2021)
Esophageal squamous cell carcinoma (ESCC) is a recalcitrant cancer. The Chinese herbal monomer fangchinoline (FCL) has been reported to have anti-tumor activity in several human cancer cells. However, the therapeutic effects and underlying mechanism on ESCC remain to be elucidated. In the present study, for the first time, we demonstrated that FCL significantly suppressed the growth of ESCC both in vitro and in vivo. Mechanistic study revealed that FCL-induced G1 phase cell-cycle arrest in ESCC is dependent on p21 and p27. Moreover, we found that FCL coordinatively triggered NOXA-dependent intrinsic apoptosis and DR5-dependent extrinsic apoptosis by transactivating ATF4, which is a novel mechanism. Our findings elucidated the tumor-suppressive effects and mechanisms of FCL and demonstrated FCL as a potential anti-ESCC agent.